(untitled) (European Journal of Economics, Finance and Business Development, 2026)
The rapid advancement of digital technologies has transformed the banking sector, offering commercial banks new opportunities to improve the efficiency of their lending activities. Digital transformation enables banks to streamline credit evaluation, enhance risk assessment, and optimize loan processing operations. This paper explores how commercial banks can leverage digital tools—including artificial intelligence, big data analytics, blockchain, and digital lending platforms—to increase lending efficiency and profitability while minimizing risks. The study also examines the challenges posed by technological integration, regulatory compliance, and cybersecurity, highlighting strategies to overcome these obstacles. Findings suggest that banks that strategically adopt digital solutions can significantly enhance their lending processes, improve customer experience, and maintain competitive advantage in the digital era.